Comparative analysis of the noncollagenous NC1 domain of type IV collagen: Identification of structural features important for assembly, function and pathogenesis. - Netzer, K.O.; Suzuki, K.; Itoh, Y.; Hudson, B.G.; Khalifah, R.G. (Protein Science, 1998)
Type IV collagen alpha1-alpha6 chains have important roles in the assembly of basement membranes and are implicated in the pathogenesis of Goodpasture syndrome, an autoimmune disorder, and Alport syndrome, a hereditary renal disease. We report comparative sequence analyses and structural predictions of the noncollagenous C-terminal globular NC1 domain (28 sequences). The inferred tree verified that type IV collagen sequences fall into two groups, alpha1-like and alpha2-like, and suggested that vertebrate alpha3/alpha4 sequences evolved before alpha1/alpha2 and alpha5/alpha6. About one fifth of NC1 residues were identified to confer either the alpha1 or alpha2 group-specificity. These residues accumulate opposite charge in subdomain B of alpha1 (positive) and alpha2 (negative) sequences and may play a role in the stoichiometric chain selection upon type IV collagen assembly. Neural network secondary structure prediction on multiple aligned sequences revealed a subdomain core structure consisting of six hydrophobic beta-strands and one short alpha-helix with a significant hydrophobic moment. The existence of opposite charges in the alpha-helices may carry implications for intersubdomain interactions. The results provide a rationale for defining the epitope that binds Goodpasture autoantibodies and a framework for understanding how certain NC1 mutations may lead to Alport syndrome. A search algorithm, based entirely on amino acid properties, yielded a possible similarity of NC1 to tissue inhibitor of metalloproteinases (TIMP) and prompted an investigation of a possible functional relationship. The results indicate that NC1 preparations decrease the activity of matrix metalloproteinases 2 and 3 (MMP-2, MMP-3) toward a peptide substrate, though not to [14C]-gelatin. We suggest that an ancestral NC1 may have been incorporated into type IV collagen as an evolutionarily mobile domain carrying proteinase inhibitor function.